2013
DOI: 10.1051/epjconf/20134003002
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of Ce3+in PbCeA (A= Te, Se, S)

Abstract: Abstract. The magnetic susceptibility of Pb 1-x Ce x A (A = S, Se and Te) crystals with 0.006 ≤ x ≤ 0.036 were studied in the temperature range from 20 mK up to room temperature. X-band (~9.5 GHz) Electron Paramagnetic Resonance (EPR) showed small shifts in the effective Landé factors that were attributed to crystal-field admixture. The EPR measurements were correlated with the magnetic susceptibility data and resulted in estimating the crystal-field splitting E( 8 ) -E( 7 ) of the lowest 2 F 5/2 manifol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The photoluminescence of Ce 3+ in various inorganic phosphors is extensively studied, but no research is found related to the GdBO 3 :Yb 3+ , Ho 3+ , Ce 3+ materials 10,33,34 . The ground state of Ce 3+ is a doublet 35 , and the lower excited states are associated with the 5d con guration. Owing to the doublet characteristics of the 4f, the emission from the ground state of Ce 3+ exhibits two overlapping bands 36 .…”
Section: Introductionmentioning
confidence: 99%
“…The photoluminescence of Ce 3+ in various inorganic phosphors is extensively studied, but no research is found related to the GdBO 3 :Yb 3+ , Ho 3+ , Ce 3+ materials 10,33,34 . The ground state of Ce 3+ is a doublet 35 , and the lower excited states are associated with the 5d con guration. Owing to the doublet characteristics of the 4f, the emission from the ground state of Ce 3+ exhibits two overlapping bands 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Diluted magnetic semiconductors (DMS) generally consist of a magnetic semiconducting material, such as II-VI or IV-VI, in which a small fraction of cations is replaced by magnetic rare-earth or transition metal ions [1][2][3][4][5][6][7][8][9]. The magnetic properties of IV-VI diluted magnetic semiconductors (DMS) containing rare earth ions with S (L = 0) state have been extensively investigated [10,11]. However, the study of IV-VI DMS containing a fraction of non Sstate rare-earth ions is much less explored [11,12].…”
Section: Introductionmentioning
confidence: 99%